O imaginário coletivo de estudantes de psicologia sobre distúrbios psicossomáticos - Volpato, Ana Lúcia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The unconscious psychological fields are organizations that influence intersubjective practices, both individual and collective. Thus, the study of the collective imagination of psychologists in training is very important, as this can interfere with their therapeutic practices. The objective of this research is investigate the collective imagination of students of fourth and fifth years of Psychology at UNESP / Assis - they were acting on stage nuclei in psychoanalytic clinic in Winnicott's approach - regarding psychosomatic disorders. The research involved the participation of 8 students, by using the procedure of Drawing-Story with Theme. Instructions for the application was: Draw a person with psychosomatic disorder. This instrument was applied through a group interview for the collective imaginary approach, which provided the possibility of survey participants get in touch and share feelings about the topic covered. After using this tool, we analyze some psychological fields and subfields of the collective imagination that emerged from productions such as the field of Feelings and the subfield of Loneliness. These fields and subfields were the object of Winnicott's psychoanalytic analysis. From our analysis, we observed that students have a basic understanding of Winnicott's theory. However, regarding the psychosomatic, his views also demonstrated restrictions. Although this has been observed, the productions have shown the value of the topics brought by them as well as the importance of other works that address these issues

Os campos psicológicos inconscientes são organizações intersubjetivas que influenciam as práticas, tanto individuais quanto coletivas. Dessa maneira, o estudo do imaginário coletivo de psicólogos em formação é muito importante, visto que tal imaginário pode interferir em suas práticas terapêuticas. Com isso, nosso objetivo foi investigar o imaginário coletivo de estudantes de quarto e quinto anos do curso de Psicologia da UNESP/Assis – que estivessem atuando em núcleos de estágio em clínica psicanalítica na abordagem winnicottiana – a respeito dos distúrbios psicossomáticos. A investigação contou com a participação de 8 estudantes, por meio do uso do Procedimento de Desenho-Estória com Tema. A instrução para a aplicação foi: “Desenhe uma pessoa com distúrbio psicossomático”. Esse instrumento foi aplicado através de uma Entrevista grupal para abordagem da pessoalidade coletiva, a qual forneceu a possibilidade dos participantes da pesquisa entrarem em contato e compartilharem sentimentos em relação ao tema abordado. Após o uso deste instrumento, analisamos alguns campos e subcampos psicológicos do imaginário coletivo que emergiram das produções, tais como o campo dos “Sentimentos” e o subcampo da “Solidão”. Estes campos e subcampos foram objeto de análise psicanalítica winnicottiana. A partir de nossa análise, pudemos verificar que os alunos em questão possuem um entendimento básico sobre a teoria winnicottiana. No entanto, no que tange à psicossomática, suas visões ainda demonstraram restrições. Ainda que isso tenha sido observado, as produções demonstraram significativamente o valor dos temas trazidos por eles, bem como a importância de outros trabalhos que tratem dessas temáticas
Keywords: Winnicott, D. W Donald Woods 1896-1971; Psicanalise; Doenças - Aspectos psicossomaticos; Imaginario; Psychosomatics